Genetic control of tyramine oxidase, which is involved in derepressed synthesis of arylsulfatase in Klebsiella aerogenes. - Oka, M (1980)
Mutants of Klebsiella aerogenes with three types of mutations affecting regulation of tyramine oxidase were isolated by a simple selection method. In the first type, the mutation (tynP) was closely linked to the structural gene for tyramine oxidase tynA). The order of mutation sites was atsA-tynP-tynA. In the second type, the mutation that relieves catabolite repression of the syntheses of several catabolite repression-sensitive enzymes are not linked to the tyn gene by P1 transduction. These strains contained high levels of cyclic adenosine 5'-monophosphate when grown on glucose. The third type of mutation, in which tyramine oxidase was synthesized constitutively, was shown by genetic analysis to involve mutations of tynP and tynR. The tynR gene was not linked to tynA. Results using the constitutive mutants showed that the constitutive expression of the tynA gene resulted in depression of arylsulfatase synthesis in the absence of tyramine.